LEADING the Way: A New Model for Data Science Education. Issue 1 (13th October 2021) - Poole, Alex H.
Abstract: Addressing the data skills gap, namely the superabundance of data and the lack of human capital to exploit it, this paper argues that iSchools and Library and Information Science programs are ideal venues for data science education. It unpacks two case studies: the LIS Education and Data Science for the National Digital Platform (LEADS‐4‐NDP) project (2017–2019), and the LIS Education and Data Science‐Integrated Network Group (LEADING) project (2020–2023). These IMLS‐funded initiatives respond to four national digital platform challenges: LIS faculty prepared to teach data science and mentor the next generation of educators and practitioners, an underdeveloped pedagogical infrastructure, scattered and inconsistent data science education opportunities for students and current information professionals, and an immature data science network. LEADS and LEADING have made appreciable collaborative, interdisciplinary contributions to the data science education community; these projects comprise an essential part of the long‐awaited and much‐needed national digital platform.